(untitled) (Journal of the College of Basic Education, 2022)
The general objective: to identify the most important personality traits that distinguished the pupils involved in handball activity, and to ascertain the existence of differences in the level of personality traits due to the academic level variable. We relied on the descriptive approach and used the scale of personality traits developed by the researcher after adapting it to the Algerian environment, and the sample size was 196 males involved in handball chosen in the intended way.To analyze the data, we used the arithmetic mean, standard deviation, and ANOVA test. We concluded that the sample members are characterized by a high level of the following traits: (extraversion, self-esteem, independence, responsibility, social adaptation, control, courage, emotional stability, persistence), and there are differences At the level of personality traits between the four academic levels (first, second, third and fourth year). The fourth year pupils are distinguished by a high level in all personality dimensions compared to other traits, Our study recommends relying on these results to select students according to the appropriate activity, and to seek to develop their personality according to these criteria.